Poetry of descendants of arabs in Latin America - Samamé B., María Olga (2012)
Arab emigration to American countries began at the end of the ninetenth century and was undertaken as the result of different negative factors due to Ottoman Turkish domination and European colonization in the Middle East. It is worth noting that among the Arabs who arrived at the New World there were intellectual pioneers who founded literary associations and stimulated the permanence of a special kind of collective Arab origin among their descendants. Literary talent began to manifest itself among the second and third generation of descendants of immigrants and continues to the present. A literature springs up in which the aim to preserve the values of Arabian culture and keep the memory of ancestors alive during a process of integration in the adopted country has prevailed. In this manner a sense of rootlessnes, nostalgia, social prejudice, adaptation and problems of custom, insertion and integration as well, lie at the base of Arab immigration into American countries and have inspired a form called “neomahyarí” that is literature created by some writers who are in fact the sons of immigrants, and whose lyrical (and also narrative) production bring together the triple impression of longing for home, serious thought and liberty.